International law and international relations - Armstrong, J. D. (James David), 1945-; Farrell, Theo, 1967-; Lambert, Helene (Cambridge : Cambridge University Press, 2012)
'In this fully updated and revised edition, the authors explore the evolution, nature and function of international law in world politics and situate international law in its historical and political context. They propose three interdisciplinary'lenses' (realist, liberal and constructivist) through which to view the role of international law in world politics and suggest that the concept of an international society provides the overall context within which international legal developments occur. These theoretical perspectives offer different ways of looking at international law in terms of what it is, how it works and how it changes. Topics covered include the use of force, international crimes, human rights, international trade and the environment. The new edition also contains more material on non-western perspectives, international institutions and non-state actors and a new bibliography. Each chapter features discussion questions and guides to further reading'--Provided by publisher.
'In this fully updated and revised edition, the authors explore the evolution, nature and function of international law in world politics and situate international law in its historical and political context. They propose three intredisciplinary'lenses' (realist, liberal and constructivist) through which to view the role of internationla law in world politics, and suggest that the concept of an international society provides the overall context within which international legal developments occur. These theoretical perspectives offer different ways of looking at international law in terms of what it is, how it works and how it changes. Topics covered include the use of force, international crimes, human rights, international trade and the environment. The new edition also contains more material on non-western perspectives, international institutions, non-state actors, and a new bibliography. Each chapter features discussion questions and guides to further reading'--Provided by publisher.
Part I. The foundations -- The nature of international law -- The evolution of international law -- Three lenses : realism, liberalism, constructivism -- Part II. The Law in World Politics -- Use of force -- Human rights -- International crimes -- International trade -- The environment -- Part III. Conclusions -- Law and power in an evolving world order.
Includes bibliographical references (p. 317-346) and index.
Keywords: International law; International relations